NiO gas sensing element prepared on needle-shaped silicon substrate. (September 2019) - Predanocy, M; Hotový, I; Mikolášek, M; Botcher, R; Spiess, L
Abstract: This study presents a new approach to enhancing the gas sensor properties based on increasing the sensing area by a structured substrate. Two types of needle-shaped silicon substrates with surface areas of 40 and 14 μm 2 were used as substrate for the preparation of NiO gas sensing element with a thickness of 25 nm. The surface morphology and composition of the prepared samples were examined by SEM, FIB-SEM, and GD OES methods. Deposited NiO films were continuous consisting of an agglomeration of small nanosized grains with arbitrary forms created on each Si needle. It was found that NiO had a polycrystalline nature. The gas sensing measurements revealed that hydrogen responses were better for NiO sensing elements prepared on needle-shape Si substrates with 40 μm 2 surface area than those with 14 μm 2 for all investigated concentrations and temperatures. The maximum relative sensitivity of 26% was measured at 250 ppm of hydrogen.